Dynamics of symptoms of genitourinary menopausal syndrome and the frequency of recurrence of lower urinary tract infection in women in periand postmenopausal patients with combined therapy with Trioginal® - D Yu Pushkar; M Yu Gvozdev (IP Berlin A.V., 2018)
Material and methods. The study included patients (n=164) in peri- and postmenopause, having a laboratory-confirmed picture of the genitourinary menopausal syndrome - atrophic vulvovaginitis and suffering from recurrent lower urinary tract infections (UTI) - cystitis and urethritis. All patients underwent standard antibacterial therapy (ABT) UTI in accordance with the results of bacteriological urine culture according to Russian clinical guidelines on urology. Against the background of ABT, 164 patients received additional therapy with Trioginal® (the study group - SG) containing estriol, micronized progesterone and Lactobacillus casei rhamnosus Doderleini 35 (LCR 35) lactobacillus strain. Trioginal® was administered intravaginally in two stages: for 20 days, 2 capsules per day, then for 10 days, 1 capsule per day. In the comparison group - CG (n=67) with ABT, Ovipol Klio® (estriol monopreparation) was additionally intravaginally used in two stages: for 14 days, 1 suppository per day, then for 2 weeks, 1 suppository 2 times a week. The control group consisted of 30 patients receiving only standard ABT UTI, local hormone therapy for vulvovaginal atrophy (VVA) was not performed. The observation period was 12 months after the end of the course of therapy. At all stages of treatment, a subjective and objective assessment of the severity of urination disorders and urogenital atrophy (UDI-6 questionnaire), their impact on the quality of life of patients (questionnaire IIQ-7), indicators of bacteriuria, bacterial urine culture and vaginal biocenosis, frequency of undesirable phenomena were carried out. According to the initial characteristics of the group of patients were comparable. Results. At all stages of the study, in the group of patients who received therapy with the use of the Trioginal® drug, there was a significant improvement in the clinical picture of urination disorders compared to the CG and the control (main) group - MG (in SG - 18% at the end of therapy versus 100% before the start of therapy; CG - 26 % versus 100% respectively; Ledger - 58% versus 100% respectively; p